Pengembangan Buku Ajar Berbasis Kearifan Lokal Ume Kabubu pada Materi Bangun Ruang untuk Meningkatkan Hasil Belajar Matematika Kelas V SD Inpres Oefau - Mercy A. Y. Tabun; Koli, Radka Bodkova; Roswita Lioba Nahak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a valid, practical, and effective Ume Kabubu local wisdom-based textbook on three-dimensional geometry to improve the mathematics learning outcomes of fifth-grade students at SD Inpres Oefau. This research employed the Research and Development (R&D) method using the Four-D (4D) model, which consists of the define, design, develop, and disseminate stages. The subjects of the field trial were 22 fifth-grade students. Data were collected through pretest and posttest instruments to measure learning outcomes and questionnaires to assess the validity and practicality of the developed textbook. The data were analyzed using descriptive statistics, paired sample t-test, and N-Gain analysis. The findings revealed that the developed textbook integrates the local wisdom values of Ume Kabubu with three-dimensional geometry materials through contextual illustrations, exercises, summaries, and evaluations. The textbook was categorized as highly valid based on expert validation results from material experts (97.5%), media experts (96.67%), and language experts (90.91%). It was also considered highly practical based on teacher assessments (87.5%) and positive student responses. The effectiveness test demonstrated a significant improvement in students' learning outcomes, indicated by a significance value of 0.000 (p < 0.05), an increase in the mean score from 50.54 in the pretest to 91.18 in the posttest, and an average N-Gain score of 0.8249, which falls into the very high category. Therefore, the developed textbook is feasible and effective for mathematics learning in elementary schools.